An Impact of Empirical Data Analysis in the World of Business Environment - Swetha, Merla; E., Naresh; Parakh, Santosh (Universitas Prasetiya Mulya, 2022)
Data Analysis plays a key role in all the fields of (Production and Operations, Finance, Marketing, Human Resource Analysis and Management) for successful market share. Data science can raise the value of any business who can effectively utilize their data. The proposed work presents heterogeneous types of data analysis techniques that are useful for changing the needs of the business. This study showcases how effective data analysis is carried out both qualitatively and quantitatively. The utilization of data analysis is to identify and distinguish the relationship in data and the trends among the factors which represent the data. It plays a vital role in making a business decision more effectively. With the aid of different data analysis techniques, data scientists can perform many operations on datasets that are useful for business organizations and it can also, help in many industrial applications.